Dinamika Komunitas Hindu Towani Tolotang di Sulawesi Selatan - Sugiarti Sugiarti (Purwadita : Jurnal Agama dan Budaya, 2020)
The Towani Tolotang community makes Hinduism its official religion. The integration of Towani Tolotang's belief into Hinduism is a long struggle to be able to maintain his existence as a Tolotang. Hinduism in the view of the Tolotang Towani Community is not only an official religion that provides legal protection for the Towani Tolotang community so that its tradition is sustainable and can appreciate the work and heritage of its ancestors, but also as a symbol of a long struggle to stay alive and survive until now. Choosing to become a Hindu is for him the struggle to become a Towani Tolotang. The joining of Towani Tolotang to Hinduism does not mean that the problem is considered over, the differences in the traditional system between the Tolotang Hindu community and Hindu traditions in other regions, especially in Bali, as if Towani Tolotang is considered as a tribal or local religion that only “hitches”  legal protection on Hinduism. In fact, it is the nature of Hinduism that does not adhere to the “law” of uniformity for its adherents, including regarding religious traditions for different ethnicities. Keywords: Dynamics, Towani Tolotang Hindu Community